2015
DOI: 10.1002/chem.201501496
|View full text |Cite
|
Sign up to set email alerts
|

Surface Activation of Pt Nanoparticles Synthesised by “Hot Injection” in the Presence of Oleylamine

Abstract: Oleylamine (OA) based “hot injection” colloidal synthesis offers a versatile approach to the synthesis of highly monodisperse metallic and multi-metallic alloyed nanostructures in the absence of potentially toxic and unstable phosphine compounds. For application in heterogeneous catalysis and electrocatalysis, the adsorbed OA species at the metal surfaces should be effectively removed without compromising the structure and composition of the nanostructures. Herein, we investigate the removal of OA from colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…The TG profile of the OAm‐capped Pt NCs recorded in synthetic air shows at least three dominant processes of decomposition from 200–380 °C, 380–450 °C, and 450–600 °C, respectively. Humphrey et al . have reported the degradation of OAm‐capped Pt/C via two stages using TGA‐MS: the cleavage of C=C to form shorter alkyl fragments and subsequently by degradation of amine and longer alkyl fragments at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The TG profile of the OAm‐capped Pt NCs recorded in synthetic air shows at least three dominant processes of decomposition from 200–380 °C, 380–450 °C, and 450–600 °C, respectively. Humphrey et al . have reported the degradation of OAm‐capped Pt/C via two stages using TGA‐MS: the cleavage of C=C to form shorter alkyl fragments and subsequently by degradation of amine and longer alkyl fragments at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various physical and chemical methods [16][17][18][19][20][21] have been developed for the removal of OAm ligand and synthesis of a surface clean platinum nanoparticle catalyst. Niu and Li [22] made a detailed review on the ligand removal and utilization for some inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Some solid supports need to be introduced to promote the sedimentation of nanoparticles, which brings new challenges to ligand removal. Humphrey et al [18] assessed the efficacies of several ligand removal methods, including chemical solvent washing and thermal pre-treatment procedures in regard to nanoparticle surface changes, and the impact of their electro-catalytic properties with regards to HCOOH and surface-adsorbed CO (CO ads ) oxidation in acidic solution. It is shown that thermal annealing treatment in H 2 or Ar atmosphere at moderate temperatures (30 0-40 0 °C) is highly effective for OAm removal.…”
Section: Introductionmentioning
confidence: 99%
“…Among metallic NPs, noble metals are popular catalyst materials due to their excellent properties [3,4]. Especially in the field of fuel cell, Pt and Pd are the most effective catalysts [5e9].…”
Section: Introductionmentioning
confidence: 99%